2015
DOI: 10.1139/bcb-2015-0030
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles alter parameters of oxidative stress and energy metabolism in organs of adult rats

Abstract: This study evaluated the parameters of oxidative stress and energy metabolism after the acute and long-term administration of gold nanoparticles (GNPs, 10 and 30 nm in diameter) in different organs of rats. Adult male Wistar rats received a single intraperitoneal injection or repeated injections (once daily for 28 days) of saline solution, GNPs-10 or GNPs-30. Twenty-four hours after the last administration, the animals were killed, and the liver, kidney, and heart were isolated for biochemical analysis. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…If the proinflammatory cascade remains effective for a longer duration, it may lead to cellular injury via the excessive generation of ROS. The intraperitoneal injection of 10 nm and 30 nm GNP caused oxidative stress and altered the energy metabolism in the liver, heart, and kidneys of the rats [ 40 ]. Following the intraperitoneal injections, 10 nm diameter GNPs significantly increased liver MDA without altering GSH levels in the rat liver on day 3 and day 7 post-dosing [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the proinflammatory cascade remains effective for a longer duration, it may lead to cellular injury via the excessive generation of ROS. The intraperitoneal injection of 10 nm and 30 nm GNP caused oxidative stress and altered the energy metabolism in the liver, heart, and kidneys of the rats [ 40 ]. Following the intraperitoneal injections, 10 nm diameter GNPs significantly increased liver MDA without altering GSH levels in the rat liver on day 3 and day 7 post-dosing [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Furthermore, oxidative stress is one of the mechanisms underlying the toxic effects of AuNPs, as also suggested for most of the nanoparticles in general. 30 -32…”
Section: Discussionmentioning
confidence: 99%
“…The data showed that sorbitol induced a significant increase in the liver catalase and serum ALT and AST, with concomitant decrease in the liver SOD activities of the treated mice. Increased catalase activity is an indication of increased oxidative stress with potential to cause more damages to the DNA, protein and lipids (Sarkar and Sil 2014;Ferreira et al 2015). Decrease in SOD activities, which is supposed to be the first line of enzyme defense against free radicals by catalyzing the dismutation of superoxide radical (O2 -) to hydrogen peroxide (H2O2) and molecular oxygen (O2) (Abdelhalim et al 2015), can subsequently lead to the accumulation of these free radicals in the biological system and hence be responsible for the observed cytogenotoxicity.…”
Section: Discussionmentioning
confidence: 99%